Risk management for drinking water supplies in developing countries :the influence of culture on water safety plans - Omar, Yahya Y. (Cranfield University, 2013)
Consumption of unsafe water in developing countries results in considerable number of illnesses and deaths annually. The World Health Organization and the International Water Association are promoting the use of water safety plans (WSPs), a risk management approach aimed at attaining water safety. This study investigated how culture impacts on the implementation of WSPs in these countries. Combining interpretive and critical paradigms resulted in the choice of qualitative methodologies utilizing multiple-case studies. Cases from India, Uganda, and Jamaica are each embedded with three units of analysis: promoters of WSPs, water utilities and their customers. Thematic analysis of data generated from semi-structured interviews, field observations and documents revealed eleven cultural factors impacting on the implementation of WSPs. Analyses of these factors led to various groupings and the subsequent development of a taxonomy categorizing these factors as being either enabling, limiting, or neutral in relation to WSPs. Findings show all the limiting factors to be deviations from the values and principles on which they are built. The findings have also led to the development of a culturally adapted risk management framework. This four-step cyclical & iterative framework is designed to address the impact of culture on the implementation of WSPs. The implementation of WSPs will take time and will require continuous improvement to the process. The successful management of drinking water risks in developing countries will require a broad institutional approach and a concerted effort that involves institutions beyond the water utilities. As such, targeted recommendations are first made towards achievement of good governance. Activities that will lead to the embracement of WSP by stakeholders along with suggestions to attain its institutionalization are also put forward. Recommendations towards addressing negative cultural factors include suggestions on dealing with: pollution causing rituals, bettering storage related practices, addressing excessive water use in rituals, counteracting belief that water should be free, fighting corruption and improving compliance, changing deliver-first safety-later attitude, and improving knowledge management practices.